Child Spacing and Children Education In Ekiti State, Nigeria - Olurotimi, Ogunlade Joseph; Ibitola, Makinde Veronica (International Journal For Research In Health Sciences And Nursing, 2016)
This study investigated the influence of child spacing on children education among the secondary school students in Irepodun/Ifelodun Local Government Area, Ekiti State. The sample consisted of one hundred parents of students randomly selected using simple random sampling techniques from different secondary schools in Irepodum/Ifelodun Local Government Area, Ekiti State, Nigeria. A self design questionnaire prepared by the researcher was used to collect data for the study. Thereafter, the data collected through the administered questionnaire were analyzed using frequency count and simple percentage which was used to find out the influence that child spacing may exert on the education of the children. The study revealed among other things the link between parent level of education and child spacing and its consequences upon children educational chances, it was recommended that couples should bear it in mind that the time interval between the births of children exert significant effect on their education. Therefore, they (couples) should seek adequate information that will help them to practice healthy pregnancy timing and proper children spacing. However, the government of the day should include sex education in the school curriculum and sponsor social workers for workshops, seminars and publications of sex education matters so as to assist people to know the healthiest child spacing techniques that will increase children educational chances.